Asymptomatic Congenital Lung Malformations: Timing of Resection Does Not Affect Adverse Surgical Outcomes - Duron, Vincent; Zenilman, Ariela; Griggs, Cornelia; DeFazio, Jennifer; Price, Jessica C.; Fan, Weijia; Vivero, Matthew; Castrillon, Juliana; Schmaedick, Maggie; Iqbal, Emaad; Rothenberg, Steven (Frontiers in Pediatrics, 2020)
Background: Optimal timing for resection of asymptomatic congenital lung malformations (CLMs) remains controversial. The aim of this study is to define optimal timing for surgical intervention of patients with CLMs and define clinical variables that affect surgical outcomes. Methods: An IRB-approved retrospective analysis was conducted for patients undergoing surgery for CLMs between 2012 and 2017. Subjects were divided into cohorts based on timing of operative intervention. “Early intervention” was defined as surgery within 4 months of birth; “intermediate intervention” - between 4 to 6 months; and “late intervention” - 6 to 12 months. Surgical outcomes including intraoperative estimated blood loss (EBL), surgical time, postoperative pneumothorax, length of time chest tube stayed in, and hospital length of stay were compared among the three groups using Fisher’s exact test or Chi-squared test for categorical variables and one-way analysis of variance test for continuous variables. Results: We analyzed 66 patients who underwent surgery for CLM. There were no significant differences in baseline characteristics. Timing of surgery did not significantly correlate with postoperative outcomes. Specifically, there was no difference in operative time, EBL, postoperative pneumothorax, or length of hospital stay among the early, intermediate, and late intervention groups. Even after controlling for cyst-volume ratio (CVR), timing of surgery still did not affect postoperative outcomes. Conclusions: Surgical outcomes for resection of CLMs are not significantly affected by timing of surgery. We advocate for early intervention to decrease the incidence of complications that can occur with later intervention.